2005
DOI: 10.1136/hrt.2003.029736
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal cardiac function during the first trimester of pregnancy

Abstract: Objective: To investigate first trimester human fetal cardiac function in relation to cardiac volume blood flow, and peripheral arterial and venous blood flow patterns. Methods: Transvaginal Doppler ultrasonography was performed in 16 uncomplicated pregnancies at 6+, 7+, 8+, 9+, and 10+ gestational weeks. The shape of the inflow waveform and the presence of atrioventricular valve regurgitation (AVVR) were noted. The outflow mean velocity (Vmean) was calculated. The proportions of the isovolumetric relaxation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
2
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 27 publications
5
56
2
9
Order By: Relevance
“…Diastolic cardiac function has been studied at mid-to late gestation, extending into the early postnatal and young adult stages. As characterized by the E/A waves across the atrioventricular valves, diastolic function matures through gestation and through the third week of postnatal life, with progressive improvements in active ventricular filling (57), similar to data found in other studies of mice and human (56,58). Thus, UBM-Doppler appears well-suited as a tool to study embryonic, fetal, and postnatal developmental cardiovascular physiology.…”
Section: Developmental Cardiovascular Physiology By Ubm-dopplersupporting
confidence: 51%
“…Diastolic cardiac function has been studied at mid-to late gestation, extending into the early postnatal and young adult stages. As characterized by the E/A waves across the atrioventricular valves, diastolic function matures through gestation and through the third week of postnatal life, with progressive improvements in active ventricular filling (57), similar to data found in other studies of mice and human (56,58). Thus, UBM-Doppler appears well-suited as a tool to study embryonic, fetal, and postnatal developmental cardiovascular physiology.…”
Section: Developmental Cardiovascular Physiology By Ubm-dopplersupporting
confidence: 51%
“…1, 2). The biphasic shape of the E/A waveform can be seen from as early as 9 weeks of gestation as documented by Mäkikallio et al [1]. …”
Section: Evaluation Of the Fetal E/a Ratiosmentioning
confidence: 61%
“…These results confirmed that cardiac compliance still increased during this gestational age range. A previous report showed that the DV blood flow showed antegrade flow during atrial contractions at a gestational age of less than 10+ weeks [12], and the fetal heart still had decreasing isovolumetric relaxation time during 11-14 weeks of gestation, indicating improving diastolic function [13]. As recommended by Bahlmann et al [14], the DV Doppler indices have greater reproducibility than only flow velocities.…”
Section: Discussionmentioning
confidence: 78%